新加坡华语的空间方位表达 ：基于语料库和问卷的实证研究 = Spatial expressions in Singapore Mandarin : a corpus- and questionnaire-based empirical study - 林书宁 Lin, Shu Ning (Nanyang Technological University, 2020)
新加坡自上世纪60年代推行双语政策，新加坡华人在保留母语的同时，英语水平也逐日加强，双语环境造成了语言之间的互相影响。 在空间表达上，汉语和英语至少有两个形式上的差异，第一个是方位词在介词短语中的使用情况，第二个是介词短语和动词之间的语序。本文将通过语料库研究和问卷调查的方式考察新加坡华人的方位词使用情况，以及介词短语和动词之间的语序偏向。 语料库研究发现新加坡华人最常使用的方位词为“上”和“里”，且偏向缺漏方位词。在介词短语和动词之间的语序方面，我们发现新加坡华人表达空间的形式上受到英语影响。 在语料库研究的基础上，本研究进行问卷调查，进一步考察新加坡华人空间表达的使用偏向。本文发现新加坡华人能够接受一些本该带有方位词，但出现缺漏情况的句子，并认为这和新加坡的双语教育有关。在介词短语和动词之间的语序方面，一些语料库中出现的说法不被问卷受试者接受，可见新加坡华人对标准语法的认知并未完全表现在日常华语语用中。 Singapore has adopted a bilingual education system since the 1960s, and Singaporean Chinese have seen an improvement in their English while retaining Mandarin as their mother tongue. The bilingual environment in Singapore resulted in the languages influencing each other. In spatial expressions, Mandarin and English differs in at least two ways. The first difference lies in the use of localizers in Mandarin prepositional phrases, and the second being the word order between the prepositional phrase and verb. This thesis studies this two areas based on data from a corpus and a questionnaire. The corpus-based study found that shang and li are the most frequently used localizers by Singaporean Chinese and there is a tendency not to use localizers. Regarding the word order between the prepositional phrase and verb, we found cases of the influence of English sentence structure when it comes to the use of spatial expressions by Singaporean Chinese. The questionnaire is designed based on the findings from the corpus study to further investigate spatial expressions among Singaporean Chinese. We found that Singaporean Chinese are acceptable to expressions without localizers even in structures where the localizers are required, and ascribed such tendency to bilingualism. We also found that some uses extracted from the corpus are rated lower in the degree of acceptance in the questionnaire, which suggests a possible mismatch between the speakers’ knowledge and actual use of Mandarin.